Streamline Garden Design: The Geometric Gardens - Jámbor, Imre (4D Journal of Landscape Architecture and Garden Art, 2007)
While analysing the works of landscape design in the past 20-30 years, there are numerous trends and intentions to be defined. The picture is considerably medley with 3 – 4 mainstreams sectioned out by their common mind. One of them is the so called geometric garden type with well defined forms and practical implements. Among these up-to-date geometric gardens there are at least three distinct trends with specific characteristic features: the so called minimal art garden, the chaotic and the nostalgic geometrical gardens.
Keywords: streamline garden; geometric garden